A nascent market for digital assets: Exploration of consumer value of NFTs - Tatiana Zalan; Elissar Toufaily (Digital Business, 2024)
Despite widespread academic and practitioner interest in non-fungible tokens (NFTs) as a form of digital assets, little is known about how consumers perceive NFT value. This exploratory research investigates why people create, trade or collect NFTs, what value they derive from them, and how online communities contribute to value co-creation. Over the course of two rounds, we interview 38 participants, most of whom are digital natives. We find that engaging with NFTs is the new form of day trading, reflecting financialization of everyday life. The value of NFTs is mainly speculative and utilitarian, and NFTs themselves are best thought of as derivatives. Value co-creation in NFT project communities is largely focused on gaining superior information about the project. We contribute to the crypto-marketing and web3 literature by advancing a novel model of NFT consumer value that extends Holbrook's (1999) typology and distinguishes both positive and negative aspects of consumer value that have been overlooked in mainstream literature. We shed light on the role of communities in an unusual setting: a nascent, illiquid, speculative, informationally opaque market for digital assets. Our study helps creators and brand managers to develop effective NFT strategies.
Keywords: 650; Blockchain; Consumer value; Digital assets; NFT; Non-fungible tokens; Speculation; web3